Severity and Its Contributing Factors in Patients With Vestibular Migraine: A Cohort Study - Liu, Wei; Dong, Hongli; Yang, Le; Zhao, Hongru; Dong, Wanli; Yang, Yi (Frontiers in Neurology, 2020)
Objective: As a recently defined disease entity, vestibular migraine (VM) is a variant of migraine with broad spectrum of manifestations. We evaluated a prospective cohort of patients with VM in two centers to assess severity of VM attacks and investigate its contributing factors in patients with VM. Methods: Adult participants with the diagnosis of VM or probable VM were enrolled according to the 2012 International Headache Society-Bárány Society Criteria. Every outpatient was followed up for six months to record the occurrence of VM attacks. Clinical data such as age, sex, number of VM attacks, severity on the visual analogue scale, and lipid intake were collected and analyzed. Generalized Anxiety Disorder-7, Patient Health Questionnaire-9, Horne and Ostberg Morningness-Eveningness Questionnaires, and Pittsburgh Sleep Quality Index were also administered to find contributing factors. Results: During a 6-month clinical follow-up, 313 VM attack were reported. According to the Visual Analogue Scale, the patients were divided into two groups. Then univariate and multivariable analyses were conducted. Among the risk factors, duration of illness (adjusted OR, 1.041; 95%CI, 1.010-1.073; P=.009), time of onset: 00:00:00-12:00:00 (adjusted OR, 3.961; 95%CI, 1.966-7.979; P<.001) and PSQI scores (adjusted OR, 1.086; 95%CI, 1.002-1.178; P=.046) were significantly associated with the severity of VM attack assessed by VAS. Conclusion: The data suggest that patients tended to experienced more severe VM attacks in early hours of a day, especially for those sufferers with longer duration of illness or poor sleep quality. Targeted management of such factors is required to reduce the severity of attacks.